KARAKTERISTIK KARBON AKTIF DARI CANGKANG BUAH KARET MENGGUNAKAN AKTIVATOR H3PO4 - Meilianti, Meilianti (Jurnal Distilasi, 2017)
This research is purposed to determine the characteristic and adsorbtion ability of activated carbon which is made from rubber fruit shell with ativator phosphoric acid ( H3PO4 ). The carbonisation of activated carbon was carried out using furnace for 1 hour with temperature of 750oC. The next mashed and sieved with a size of 100 mesh. Then activated for 24 hours with H3PO4 solution with variation of concentration , 8%,  8.5%,  9%,  9.5% and    10%. As the result of characterisation, the lowest water degree wash content 10% with the value  3,25 % and lowest volatille metter from sample 10 % with the value 3,15 %. the lowest ash degree was from sample 8 % with the value 3,36 %. Maximum adsorbtion of iodine with sample 10  % with the value 947,25  mg/g . The optimum condition of activated carbon with activator phosphoric acis, which is produced in concentration 10%. Which at this concentration has moisture water degree of 3,25%, ash degree of 3,36%, volatille metter degree 3,15%, absorption iodine of 947.25 mg / g, and absorption metilene blue 98,95 mg/g.